Development and cytology of pollen in Dahlstedtia Malme (Leguminosae : Papilionoideae) - Teixeira, S. D.; Forni-Martins, E. R.; Ranga, N. T. (Elsevier B.V., 2002)
Microsporogenesis, chromosome number, meiotic behaviour and meiotic index were investigated in Dahlstedtia pinnata and D. pentaphylla, two legume species occurring largely in Brazil, in order to ascertain whether the pollen could limit fertilization events. Archesporial cells originate primary sporogenous and anther wall precursor cells, the tapetum is uniseriate, uninucleate and glandular. Tetrads are tetrahedric or decussate, and cytokinesis is of the simultaneous type. Mature pollen grains are tricolpate and bicellular. No abnormalities in microsporogenesis were found. In both species the chromosome number is n = 11, a number not reported previously. The base number for Dahlstedtia is also 11, because cytological observations include both species of Dahlstedtia. D. pentaphylla has a higher meiotic index and lower individual variation values, and it is considered meiotically stable. Its pollen grains do not limit fertilization. D. pinnata has a lower meiotic index, and the pollen is one of the factors which limit fertilization. Furthermore, D. pinnata has numerous adventitious shoots, which suggest that vegetative propagation is important in its reproductive process. (C) 2002 the Linnean Society of London, Botanical Journal of the Linnean Society, 2002, 138, 461-471.
Keywords: anther walls; chromosome number; fertilization success; meiotic abnormalities; meiotic index; microsporogenesis; tapetum